Caracterización del rol de la MAP quinasa fosfatasa 1 (MKP-1) en la regulación de la respuesta al estrés de retículo endoplásmico - Cabrera Escobar, Luciana Andrea (2019)
GRP78 protein is a crucial marker of endoplasmic reticulum stress (ER) and its early induction is registered with different inductors of ER stress. In this work, we analyzed the role of MAP Kinases (MAPK) and MAP Kinases Phosphatases (MKP) on the induction of GRP78 by cisplatin (CPT) in the HK-2 cell line derived from human kidney cells. CPT causes a significant increase on GRP78 mRNA levels after 3 h of exposure. Thus, GRP78 mRNA levels were analyzed in CTP-treated cells in the presence of well-characterized inhibitors of ERK1/2, JNK, and p38 activation. Only PD98059, an inhibitor of ERK1/2 activation, significantly reduced CPT-induced GRP78 mRNA levels. Accordingly, CPT transiently increased phospho-ERK1/2 levels in a time-dependent manner. Also, CPT transiently increased the expression of MKP-1, a phosphatase that dephosphorylates ERK1/2, JNK, and p38, in a time frame that coincides with ERK1/2 dephosphorylation. To demonstrate the potential modulatory role of MKP-1 on GRP78 induction, the effect of MKP-1 overexpression on GRP78 mRNA levels induced by CPT was also analyzed. HK-2 cells were transiently transfected with a plasmid designed for the expression of a tagged form of MKP-1 (flag-MKP-1) under a constitutive promoter, or with empty plasmid (PV) as control. MKP-1 overexpression reduced CPT-mediated GRP78 induction. Moreover, MKP-1 overexpression reduced the viability of CPT-exposed cells.\nIn summary, exposure of HK-2 cells to CPT for short periods of\ntime (6 h) results in GRP-78 induction through an ERK-dependent mechanism. CPT induces also MKP-1, which contribute to modulate the activity of ERK1/2 and therefore, the ERK-dependent events that are integral components of the response to ER stress.